TWO STAGE ADAPTIVE MOTION-COMPENSATED FILTER FOR NOISY IMAGE SEQUENCES (Sciences & Technologie. B, Sciences de l'ingénieur, 2003)
In this paper, we propose a new technique for motion compensated filtering of noisy image sequences which aims to achieve an efficient noise reduction without introducing blurring artefacts. The technique consists in a cascade of the versions of the temporal and the spatiotemporal Adaptive Weighted Averaging (AWA) filter proposed in [11]. We referred the technique as a Two-Stage AWA filter (TS-AWA) [1][2]. The process consists in: first, the noisy observation is filtered temporally using the temporal AWA filter (AWA 1-D) along a large motion compensated temporal support. Second, the resulting image sequence is then processed by the spatiotemporal AWA filter (AWA 3-D) along a smaller support which the motion trajectories are estimated after the first stage. In each stage, motion trajectories are estimated with a modified block matching motion estimation algorithm [3]. Simulation results show that the proposed TS-AWA filter outperforms the AWA 3-D filter in both terms of visual quality and Signal to Noise Ratio improvement.